Synthesis of Silsesquioxanes with Substituted Triazole Ring Functionalities and Their Coordination Ability - Monika Rzonsowska; Katarzyna Kozakiewicz; Katarzyna Mituła; Julia Duszczak; Maciej Kubicki; Beata Dudziec (Molecules, 2021)
A synthesis of a series of mono-T8 and difunctionalized double-decker silsesquioxanes bearing substituted triazole ring(s) has been reported within this work. The catalytic protocol for their formation is based on the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) process. Diverse alkynes were in the scope of our interest—i.e., aryl, hetaryl, alkyl, silyl, or germyl—and the latter was shown to be the first example of terminal germane alkyne which is reactive in the applied process’ conditions. From the pallet of 15 compounds, three of them with pyridine-triazole and thiophenyl-triazole moiety attached to T8 or DDSQ core were verified in terms of their coordinating properties towards selected transition metals, i.e., Pd(II), Pt(II), and Rh(I). The studies resulted in the formation of four SQs based coordination compounds that were obtained in high yields up to 93% and their thorough spectroscopic characterization is presented. To our knowledge, this is the first example of the DDSQ-based molecular complex possessing bidentate pyridine-triazole ligand binding two Pd(II) ions.